Banished Men How Migrants Endure the Violence of Deportation - Andrews, Abigail (University of California Press, 2023)
What becomes of men the U.S. locks up and kicks out? From 2009 to 2020, the U.S. deported more than five million people-over 90 percent of them men. In Banished Men, Abigail Andrews and her students tell 186 of their stories. How, they ask, does expulsion shape men's lives and sense of themselves? The book uncovers a harrowing carceral system that weaves together policing, prison, detention, removal, and border militarization to undermine migrants as men. Guards and gangs beat them down, till they feel like cockroaches, pigs, or dogs. Many lose ties with family. They do not go "home." Instead, they end up in limbo: stripped of their very humanity. Against the odds, they fight for new ways to belong. At once devastating and humane, Banished Men offers a clear-eyed critique of the violence of deportation. "Banished Men is beautifully written, bringing deported men to life in all their misery and hopes. It is a timely contribution to immigration and Latinx sociology literatures, as well as an intervention in how to do collective social-justice-oriented research." - NANCY PLANKEY-VIDELA, Professor of Sociology and Coordinator of Latino/a and Mexican American Studies at Texas A&M University "Banished Men asks what becomes of men-their emotions, relationships, family ties, economic opportunities, and very sense of self-as they are forced to live through U.S. detention, imprisonment, and deportation. This powerful book delves into how banishment upends men's lives and shapes their humanity." - JENNIFER RANDLES, author of Essential Dads